The Urgency of Interactive Learning Multimedia for Students' Visual Spatial Intelligence - Annisa Eka Fitriani Hidayat; Wati Susilawati; Ida Nuraida (Gunung Djati Conference Series, 2022)
The purposei ofi thisi studyi isi toi knowi abouti multimediai interactivei ini mathematicali learning,i thei positive impacti ofi interactivei multimediai learningi oni studentsi andi thei importancei ofi interactivei learningi aboutii student’si spatial visual intelligence.i Thei researchi methodi usedi isi ai qualitativei researchi methodi throughi literaturei review.i Thei resulti showedi thati thei multimediai interactivei ini mathematicali learningi cani bei computeri applications,i mathematicali software’si andi applicationsi createdi byi teachersi themselves,i wherei interactivei multimediai learningi givesi ai positivei impacti ini mathematicali learningi becausei iti cani makei learningi interestingi andi innovative,i furthermorei studentsi willi alsoi bei motivatedi ini learningi soi thati studenti mathematicali abilityi andi resulti ofi learningi willi increase.i Thei mathematicali learningi withi multimediai interactivei is fundamentali cause can gives ani impacti thei developmenti andi increasesi ofi studentsi visuali spatiali intelligence,i withi thei interactivei multimediai learning,i thei abstracti ofi mathematicali objectsi cani bei concrete visualized